2023
DOI: 10.1088/1361-6560/acabfe
|View full text |Cite
|
Sign up to set email alerts
|

TOPAS simulations of the response of a mini-TEPC: benchmark with experimental data

Abstract: Objective: Microdosimetry offers a fast tool for radiation quality (RQ) verification to be implemented in treatment planning systems in proton therapy based on variable LET or RBE to move forward from the use of a fixed RBE of 1.1. It is known that the RBE of protons can increase up to 50% higher than that value in the last few millimetres of their range. Microdosimetry can be performed both experimentally and by means of Monte Carlo (MC) simulations. This paper has the aim of comparing the two approaches. App… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…However, we primarily employed two sizes of scoring spheres: a 1 μm radius sphere made of water and a 6.35 mm radius sphere made of tissue-equivalent gas. Notably, studies by Zhu et al (2019), Bianchi et al (2023), Missiaggia et al (2023a) have demonstrated that microdosimetric spectra simulated with a TEPC detector align well with experimental data. The 1 μm radius water sphere was used to construct the LUTs and replicate the PIDE cell survival data.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…However, we primarily employed two sizes of scoring spheres: a 1 μm radius sphere made of water and a 6.35 mm radius sphere made of tissue-equivalent gas. Notably, studies by Zhu et al (2019), Bianchi et al (2023), Missiaggia et al (2023a) have demonstrated that microdosimetric spectra simulated with a TEPC detector align well with experimental data. The 1 μm radius water sphere was used to construct the LUTs and replicate the PIDE cell survival data.…”
Section: Discussionsupporting
confidence: 53%
“…In Zhu et al (2019) the microdosimetric extension of TOPAS has been implemented, allowing to score of lineal energy y with three different types of detectors: (i) spherical Tissue Equivalent Proportional Counter (TEPC), (ii) a cylindrical TEPC (also known a mini-TEPC) and (iii) Silicon on Insulator (SOI) microdosimeter. These detectors are the reference detectors for microdosimetry, (Bradley et al 2001, De Nardo et al 2004, Debrot et al 2018, Bianchi et al 2022, Missiaggia et al 2020, 2023a. The microdosimetric extension offers to the user the possibility to save microdosimetric spectra (yf (y) and yd(y)) and the relative average quantities (y F and y D ) for each detector, including the contribution of the particle species of the radiation field.…”
Section: Topasmentioning
confidence: 99%
“…They are particularly well suited to microdosimetry as they can describe the stochastic nature of particle interactions and energy depositions. They have been used to characterize detectors for microdosimetry, including tissue equivalent proportional counters (TEPCs), silicon and diamond microdosimeters, and thermoluminescence detectors (TLDs), and to calculate microdosimetric quantities in radiation fields of interest (e.g., Bachiller-Perea et al , 2022; Baratto-Roldán et al , 2021; Bianchi et al , 2023; Böhlen et al , 2011; Bolst et al , 2017; 2018; 2020b; Bortot et al , 2018; Burigo et al , 2013; 2014; Conte et al , 2020; Dos Santos et al , 2020; Fattori et al , 2022; Hugtenburg et al , 2007; Kyriakou et al , 2017; Lindborg et al , 2022; Markovic et al , 2020; Matsuya et al , 2022; Mazzucconi et al , 2018; Missiaggia et al , 2023; Nikjoo et al , 1989; 1991; 1994a; 2007; Northum et al , 2012; Oliver and Thomson, 2018; Parisi et al , 2019; 2022; Petringa et al , 2020; Poignant et al , 2022a; Rollet et al , 2004; 2010; Sato et al , 2021b; Selva et al , 2022; Stewart et al , 2002; Vohradsky et al , 2021; among others).…”
Section: Monte Carlo Simulations For Microdosimetrymentioning
confidence: 99%
“…The following criteria were adopted to select this in vitro dataset: (A) the cell line used was non-synchronized, (B) the cell exposures were carried out at different positions (i.e. different LET) along a monoenergetic proton beam, (C) the (residual) proton energy at target position was at least 1 MeV, and (D) radiation quality information (LET and lineal energy) was available in literature to benchmark the results of our physical calculations (Chaudhary et al 2014, James et al 2021, Bianchi et al 2023. The PlotDigitizer Online App was used to extract the data from the published plots reporting the physical quantities used to benchmark our simulations (https://plotdigitizer.com/app).…”
Section: Human Glioblastoma Cellsmentioning
confidence: 99%